Strategic Determinants of Service Quality and Performance: Evidence from the Banking Industry - Roth, Aleda V.; Jackson, William E. (Management Science, 1995)
This paper focuses on an important new service management strategy: the operations capabilities-service quality-performance (C-SQ-P) triad. In order to understand what generic operations capabilities influence the strategic behavior of high performing service firms, we explore three related questions: What generic operations capabilities are among the strategic determinants of service quality? Does service quality affect market performance? How is market conduct related to the C-SQ-P triad? These questions are investigated using a stylized capabilities-based model of service quality that simultaneously assesses their impact upon a firm’s market performance. Several insights emerge from our research: a) generic operations capabilities affect service quality and performance, although not all relationships are direct; b) service quality know-how and innovations can be directly observed and imitated; c) the effects of technological leadership and market acuity on service quality are moderated by the absorptive capacity of employees to recognize and exploit their potential, and hence, investments in people are critical to success; d) market conduct influences the generic capabilities of the firm more than market performance, ceteris paribus; and e) total factor productivity and service quality are negatively correlated.